Outcome-Based Education in Primary Islamic School Teacher Education: Curriculum Practices and Influencing Factors - Rizqiatin Rosa; Dzakiyah Ali Kusuma Pradani; Nur Hidayatus Sholihah; Alfarobi Ahmad Sulaiman; Wahid Murni; Samsul Susilawati (Yayasan Darussalam Bengkulu, 2026)
Outcome-Based Education (OBE) requires higher education programs to align intended graduate competencies, teaching, and assessment, yet evidence from Islamic higher education remains limited on how established curricula are optimized after initial adoption. This study investigated OBE-based curriculum optimization in the Elementary Madrasah Teacher Education Study Program at Universitas Islam Negeri Maulana Malik Ibrahim Malang and identified the factors enabling and constraining this process. A qualitative single-case design involved five purposively selected informants: the head of the study program, the program secretary, and three lecturers. Data were generated over one month through in-depth interviews, observation, and analysis of Semester Learning Plans, syllabi, and related curriculum documents. The data were examined through iterative reduction, interpretation, and conclusion drawing, while source and technique triangulation supported credibility. The findings identified four optimization practices: aligning Graduate Learning Outcomes (CPL), Course Learning Outcomes (CPMK), and Sub-CPMK; incorporating alumni, graduate-user, and tracer-study input; strengthening lecturer commitment and integrity; and using authentic assessment. Supporting conditions included curriculum documentation, lecturer training and mentoring, stakeholder engagement, and national regulatory support. The principal constraints were the absence of a standardized instrument for measuring CPL attainment and uneven lecturer commitment. The study shows that optimization has progressed at the level of curriculum architecture and reported implementation, but its effects on graduate competence cannot yet be verified without validated attainment data. It therefore highlights the need to connect documentary OBE compliance with measurable classroom enactment and learning outcomes.